هدنة ريتهوند ونهاية الحرب العالمية الأولى 1914-1918 - ورتي، جمال (جامعة الانبار - كلية التربية للعلوم الإنسانية, 2021)
يتناول موضوع هذا المقال بالدراسة والبحث والتحليل سبب توقيع ألمانيا على هدنة ريتهوند في 11 تشرين الثاني 1918 التي أنهت الحرب العالمية الأولى، بين ألمانيا وممثلها ماثياس أرز بيرغر (Matthias Erzberger) والحلفاء وممثلهم الجنرال فرديناند فوش (Ferdinand Foch) في غابة كومبين (Compégne) وفي العربة الحديدية، وسنحاول إماطة اللثام عن التطورات السياسية والعسكرية التي عرفتها السنتان الأخيرتان من الحرب في ألمانيا ودول الحلفاء، إذ انسحبت روسيا منها بمقتضى معاهدة برست لتوفسك (Brest –Litovsk) في 03 آذار 1918 نتيجة الثورة البلشفية، كما دخلت الولايات المتحدة الأمريكية الحرب إلى جاب الحلفاء في شهر نيسان 1917، وقد كان لإعلان مبادئ الرئيس الأمريكي ويلسون عن مبادئه الأربعة عشر في 08 كانون الثاني 1918 التي تضمنت إحداها حق الشعوب في تقرير مصيرها، وكذا ظهور الاشتراكية كنظام سياسي واقتصادي جديد فكان لانتشاره دور في تغيير الكثير من المفاهيم والحقائق خاصة في ألمانيا، إذ سقط الرايخ الثاني (1871-1918) نتيجة ثورة اشتراكية داخلية حدثت قبيل نهاية الحرب وكانت بدعم العديد من المفكرين خاصة الكاتبة روزا لكسمبورغ (Luxemburg Rosa) وكارل ليبيكنخت (Liebknecht Karl)، وقام في ألمانيا نظام جمهوري عقد الهدنة مع الحلفاء وبعدها معاهدة فرساي في 28 حزيران 1919، وقد كان لظروف توقيع هدنة ريتهوند ومعاهدة فرساي دور بالغ في تنامي الشعور القومي الألماني إذ كانت الفترة الممتدة بين الحربين (1919-1939) قد نضجت فيها الأسباب التي أدت إلى الحرب العالمية الثانية وسببا رئيسيا في إجبار فرنسا على توقيع هدنة ريتهوند ثانية في 22 حزيران 1940 في غابة كومبين وفي العربة الحديدية نفسها التي وقعت فيها ألمانيا على الهدنة سنة 1918.
The present research paper is an attempt to shed some light on the causes of Germany’s ratification of the Armistice of Rethondes on November 11th, 1918 that ended fighting in World War I. The armistice was signed by the German civilian politician Matthias Erzberger and the Allied Supreme Commander, Marshall Ferdinand Foch in a railroad carriage at Compiègne forest. The paper will clarify the political and military developments during the last two years of the war between Germany and the Allies, mainly with the withdrawal of Bolshevik Russiaafter the Treaty of Brest-Litovsk on Marsh 3rd, 1918. The United States of America took part in the war by the side of the Allies in April 1917 after the American President Wilson’s fourteen principles had been outlined on January 14th, 1918 among which the right of people to self determination. The upheaval of socialism as a new political and economic system brought many conceptual changes mainly in Germany and the end of the German Reich (1871-1918) due to a socialist revolution prior to the war supported by Rosa Luxemburg and Karl Liebknecht. Henceforth, came a republican government and signed f the armistice with the Allies first and then the Treaty of Versailles on June 28th, 1919. Indeed, the signature of the Armistice of Rethondes and the Treaty of Versailles nurtured the German nationalism between 1919 and 1939 paving the way to World War II and the ramification of a second Armistice of Rethondes by France, this time, on June 22nd, 1940 at Compiègne forest in the same railroad carriage where Germany, in 1918) signed the first armistice.
Keywords: المعاهدات الدولية -- هدنة ريتهوند -- الحرب العالمية الأولى -- ألمانيا